Combined effects of carbide, cavitation and thin-section size on the creep rupture properties of a nickel-base superalloy - Baldan, Ahmet (Carl Hanser Verlag GmbH & Co, 1994)
The combined effects of thin-section size, carbide and cavitation dispersion on the creep rupture characteristics of the conventionally cast MAR-M002 superalloy have been studied at 1173 K/300 MPa. It was shown experimentally that the creep rupture life of the alloy is controlled by the (ac/ao)/D ratio, where ac is the cavity size, ao the carbide particle size and D the diameter of the gauge section of specimen. Below a critical value (? 100 × 10-6 ?m-1) of this ratio the rupture life extends rapidly, whereas above the critical value of the ratio there is a slow increase in the rupture life. The effect of the (ac/ao)/D ratio on the rupture life has been described using the existing theories which were developed for the prediction of stress concentrations at grain boundary particles.
Keywords: Carbides; Composition effects; Crack propagation; Creep; Crystals; Deformation; Grain boundaries; Mathematical models; Melting; Metallographic microstructure; Nickel; Particle size analysis; Carbide formation; Carbide networks; Cavitation dispersion; Combined effects; Conventionally cast blade alloys; Creep rupture properties; Rupture life; Superalloys